OP0051 Evolution of the vascular involvement objectified by pet/tac in patients with giant cell arteritis treated with tocilizumab. (12th June 2018) - Prieto-Peña, D.; Loricera, J.; Martín-Varillas, J.; Calderón-Goercke, M.; Nárvaez, J.; Aurrecoechea, E.; Villa, I.; Castañeda, S.; Gómez-Arango, C.; Mera, A.; Pérez-Pampín, E.; Aldasoro, V.; et al.
Abstract : Background: Giant cell arteritis (GCA) is a large-vessel vasculitis which can involve the aorta and/or its major branches. Tocilizumab (TCZ) seems to be effective in giant cell arteritis (GCA). 1–4 Objectives: Our aim was to assess if the clinical and analytical improvement yielded in patients with GCA treated with TCZ is accompanied by a reduction of the vascular inflammation evaluated by PET/CT. Methods: Study of 36 patients who had a baseline and follow-up PET/CT from a multicenter series of 134 patients with GCA in treatment with TCZ. The evolution of the vascular involvement objectified by PET/CT was assessed. In addition clinical efficacy, analytical improvement (acute phase reactants) and the reduction of corticosteroid dose was studied. Results: The 36 patients (28 women and 8 men) had an mean age of 69.83±8.66 years. After TCZ onset, a rapid and maintained clinical improvement was observed (table 1). In addition, during the first twenty-four months of follow-up, C-reactive protein decreased from 2.4 [0.9–6.8] to 0.1 [0.0–0.5] mg/dL and the erythrocyte sedimentation rate from 41.5 [16.7–58.5] to 4 [2–12.5] mm/1 st hour. On the other hand, the levels of haemoglobin experienced an increase from 12.3 [11.3–13.0] to 13.3 [13.0–13.9] g/dL. The median dose of prednisone decreased from 12.5 [9.4–26.2] to 0.0 [0.0–0.0] mg/day. However, the decrease in F18-fluordeoxyglucose uptake in the PET/CT study was not as evident. Conclusions: Although TCZ seems to be an important therapeutic agent in the treatment of GCA, achieving a rapid and sustained clinical and analytical improvement, the decrease in vessel inflammation assessed by F18-fluordeoxyglucose uptake seems to take a slower course. References: [1] Loricera J, et al. Tocilizumab in giant cell arteritis: Multicenter open-label study of 22 patients. Semin Arthritis Rheum2015;44:717–723. [2] Loricera J, et al. Tocilizumab in refractory aortitis: Study on 16 patients and literature review. Clin Exp Rheumatol2014;32(3 Suppl 82):S79–89. [3] Loricera J, et al. Use of positrón emission tomography (PET) for the diagnosis of large-vessel vasculitis. Rev Esp Med Nucl Imagen Mol2015;34:372–377. [4] Loricera J, Blanco R, Hernández JL, et al. Tocilizumab in patients with Takayasu arteritis: A retrospective study and literature review. Clin Exp Rheumatol2016;34(3 Suppl 97):S44–53. Disclosure of Interest: None declared